Meeting Report From the 2016 11th Biennial Ovarian Cancer Research Symposium: Mechanisms of Initiation and Progression of Ovarian Cancers. (1st November 2017) - Chien, Jeremy; Mehta, Geeta
Abstract : Objective: The aim of this study was to review the latest research advances on the mechanisms of initiation and progression of ovarian cancer. Methods: At the 11th Biennial Ovarian Cancer Research Symposium, which was held in Seattle, Washington in September 2016, leaders in ovarian cancer research convened to present and discuss current advances and future directions in ovarian cancer research. Results: One session was dedicated to Mechanisms of Initiation and Progression of Ovarian Cancer, and included a keynote presentation from Dr Ronny Drapkin, MD (University of Pennsylvania), and an invited oral presentation from Laising Yen, PhD (Baylor College of Medicine). Nine additional oral presentations were selected from abstract submissions. Thirty-three abstracts were presented in poster format and were grouped into the categories of mechanisms of the genesis of genomic instability, tumor initiation, metastases of ovarian cancers, innate and acquired chemotherapy resistance, tumor progression, tumor-initiating cell and chemotherapy resistance, and immunomodulation. Conclusions: Eradication of ovarian cancers requires clear understanding of molecular mechanisms of ovarian cancer initiation and progression. These mechanisms will not only drive the precision of early detection, but also discovery of new therapies to target precursor lesions and more advanced stage disease.